Actio Confessoria for Protection of easement - Popov, Danica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The Law on Fundamentals of Property Relations, prescribes the possibility of raising two lawsuits to protect the easement.  The lawsuit for the establishment, the owner of the dominant tenement may demand that according to the owner of the servient tenement, establish the existence of easements. In another case, the owner of the dominant tenement which unreasonably prevents or obstruct easement with lawsuit to demand termination of acts which prevents or disturbed, while performing easement. In addition to the petitory protection, the right holder of easements, has the right to the protection of possession, and obligation lawsuits for damages caused by the actions of the owner of the servient tenement or any third persons, and lawsuit for enforcement of obligations under the contractual relationship of the establishment of easement. The subject of this work is the protection of real easement confessoria lawsuits as follows: Lawsuit to establish easement, actio confessoria publiciana and actio negatoria confessoria.